A Good Night’s Sleep: Learning About Sleep From Autistic Adolescents’ Personal Accounts - Pavlopoulou, Georgia (Frontiers in Psychology, 2021)
Background: Sleep is a strong predictor of quality of life and has been related to cognitive and behavioural functioning. However, research has shown that most autistic people experience sleep problems throughout their life. The most common sleep problems include sleep onset delay, frequent night-time wakings and shorter total sleep time. Despite the importance of sleep on many domains, it is still unclear from first-hand accounts what helps autistic people to sleep. The purpose of this study is to explore together with autistic adolescents their sleep-related practices before bedtime and during the day which contribute to a good night’s sleep. Methods: Fifty-four autistic adolescents collaborated with an academic researcher in a novel adapted photo-elicitation methodology, rooted in a Lifeworld framework. The adolescents were invited to collect and analyse their data. The data were also presented in a community knowledge exchange event. Results: Several self-reported practices that facilitate better nocturnal sleep were identified. Those were organised into two thematics: Evening/bedtime factors and Day time factors. These included practices such as personalised sensory and relaxation tools before bed and during night-time, engaging in a range of physical activities during daytime and accommodating personal time to engage with highly preferred and intense focus activities and hobbies. It also included spending time in predictable and fun ways with family members before bedtime. Conclusions: This is the first time that a study uses a novel methodological approach based on personal accounts elicited by photos rooted in a Lifeworld framework to describe personal sleep-related practices before bedtime and during the day to identify a “good night of sleep” in autistic adolescents. The outcomes from the current study showed that sleep facilitating factors are in a direct contrast to the sleep hygiene recommendations. Therefore, it is thus important for the sleep practitioners and healthcare providers to move beyond providing standardised sleep hygiene interventions. A Lifeworld led care model that pays attention to personal experiences, promotes sense of agency, evaluates both autism-specific strengths and struggles could and should complement biomedical approaches.